The challenge of transformation : an analysis of the ethical and strategic need for transformation with special reference to the Employment Equity Act - Reed, Stephen Graham (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--University of Stellenbosch, 2003.